Pharmacokinetic Properties of Adenosine Amine Congener in Cochlear Perilymph after Systemic Administration - Chang, Hao (Biomed Res Int, 2017)
Noise-induced hearing loss (NIHL) is a global health problem affecting over 5% of the population worldwide. We have shown previously that acute noise-induced cochlear injury can be ameliorated by administration of drugs acting on adenosine receptors in the inner ear, and a selective A(1) adenosine receptor agonist adenosine amine congener (ADAC) has emerged as a potentially effective treatment for cochlear injury and resulting hearing loss. This study investigated pharmacokinetic properties of ADAC in rat perilymph after systemic (intravenous) administration using a newly developed liquid chromatography-tandem mass spectrometry detection method. The method was developed and validated in accordance with the USA FDA guidelines including accuracy, precision, specificity, and linearity. Perilymph was sampled from the apical turn of the cochlea to prevent contamination with the cerebrospinal fluid. ADAC was detected in cochlear perilymph within two minutes following intravenous administration and remained in perilymph above its minimal effective concentration for at least two hours. The pharmacokinetic pattern of ADAC was significantly altered by exposure to noise, suggesting transient changes in permeability of the blood-labyrinth barrier and/or cochlear blood flow. This study supports ADAC development as a potential clinical otological treatment for acute sensorineural hearing loss caused by exposure to traumatic noise.